(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
The bender element is one of the most useful geophysical tools used in the laboratory to measure soil dynamics properties in a non-destructive way. However, inconsistent testing procedures may produce unrepeatable test results. Therefore, understanding the effect of the sensor rotation between the source and receiver position is crucial. This effect was evaluated using polystyrene material, which was unchanged throughout the period of testing. With sensor rotation angle starting from 00 to 900, the P-wave and S-wave velocities were calculated using five methods (Visual, First-peak, Maximum-peak, CCexcel and CCGDS). The cross-correlation methods are used in two ways; by using normalized cross-correlation in Excel (knowned as CCexcel) and by using GDS (Geotechnical Digital Systems Company for supplying Geotechnical instrument) bender element analysis tool BEAT (knowned as CCGDS). The results show that the Visual and First-peak methods gave a consistent wave velocity compared to the three other methods. In addition, both calculation methods were not significantly affected by increasing the sensor rotation angles. However, the Maximum-peak showed significant effect when the sensor rotation angle was above 200. The same issue was recognized for both cross-correlation methods when the sensor rotation angle was above 500. Moreover, the results from damping-slope indicated low effects for increasing the sensor rotation at P-wave and S-wave with sample thickness of 62.58 mm and 88.97 mm respectively (with an average damping-slope of about 3.50). In addition, the effect of the sensor rotation became more obvious at P-wave and S-wave with sample thickness of 88.97 mm and 62.58 mm respectively (with variation in the damping-slope 0.40 to 41.20).